2021
DOI: 10.1155/2021/9985919
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Relationship between Fracture Morphology and Splitting Strength of Granite Based on Fabric Distribution

Abstract: Because of the requirement of the mechanical properties of the damaged surrounding granite rock and the existence of the fracture water in hydraulic fracturing engineering, the strength of granite is related to the fabric, and the roughness of the section is also related to the liquid flow rate, a method of roughly determining the strength of the specimen by observing the failure mode of rock is needed. Considering that the physical and mechanical properties of granite are obviously affected by the fabric, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…21 Du et al found that the strength of granite is related to the roughness of the section and established a method to determine the strength of specimens approximately by observing the damage pattern of the rock. 22 Chinnasamy et al investigated the effect of cryogenic treatment of rock cutting bits microstructure with different soaking time and analyzed the treatment mechanism. 23,24 Zheng et al and Tan et al conducted percolation tests on sandstone rock samples with different water saturation and studied the relationship between permeability, porosity, and stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Du et al found that the strength of granite is related to the roughness of the section and established a method to determine the strength of specimens approximately by observing the damage pattern of the rock. 22 Chinnasamy et al investigated the effect of cryogenic treatment of rock cutting bits microstructure with different soaking time and analyzed the treatment mechanism. 23,24 Zheng et al and Tan et al conducted percolation tests on sandstone rock samples with different water saturation and studied the relationship between permeability, porosity, and stress.…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al analyzed the variation law of mechanical properties and roughness properties of splitting surface of granite, and established the fitting curve between tensile strength and roughness properties 21 . Du et al found that the strength of granite is related to the roughness of the section and established a method to determine the strength of specimens approximately by observing the damage pattern of the rock 22 . Chinnasamy et al investigated the effect of cryogenic treatment of rock cutting bits microstructure with different soaking time and analyzed the treatment mechanism 23,24 .…”
Section: Introductionmentioning
confidence: 99%